Do older drivers with bilateral cataract self-regulate their driving while waiting for first eye cataract surgery? - Agramunt, S.; Meuleners, Lynn; Fraser, M.; Chow, Kyle; Ng, Jonathon; Raja, V.; Morlet, Nigel (Dove Medical Press Ltd., 2017)
Objectives: To analyze the association between visual impairment and driver self-regulation among a cohort of older drivers waiting for first eye cataract surgery. Methods: Ninety-six drivers with bilateral cataract aged 55+ years were assessed before first eye cataract surgery. Data collection consisted of a researcher-administered questionnaire, objective visual measures (visual acuity, contrast sensitivity and stereopsis), a visual attention test (the useful field of view test) and a cognitive test (the Mini-Mental State Examination). Driver self-regulation practices were collected using the Driving Habits Questionnaire and were also measured with an in-vehicle monitoring device. Characteristics of self-regulators and non-self-regulators were compared and a logis tic regression model was used to examine the association between 3 objective visual measures and driver self-regulation status. Results: After controlling for potential confounding factors, only binocular contrast sensitivity (p=0.01), age (p=0.03) and gender (p=0.03) were significantly associated with driver self-regulation status. The odds of participants with better contrast sensitivity scores (better vision) self-regulating their driving in at least 1 driving situation decreased (odds ratio [OR]: 0.01, 95% CI: 0.00-0.28) while those of increasing age reported an increased odds of self-regulating their driving (OR: 1.08, 95% CI: 1.01-1.15). The odds of males self-regulating their driving was decreased compared with females (OR: 0.28, 95% CI: 0.09-0.86). Conclusions: Worse binocular contrast sensitivity scores, increasing age and being female were significantly associated with driver self-regulation. The study highlighted that while self-regulation was common among cataract patients, a proportion of those with poor vision did not self-regulate. Further research should determine how cataract patients could benefit from self-regulation strategies while waiting for cataract surgery.